Unraveling the Mystery of Data: The Role of Statistics in Big Data Analytics - Dermawan, Andri; Ambiyar, Ambiyar; Zaus, Mahesi Agni (Southeast Asian Journal of Technology and Science, 2021)
This article explores the crucial role of statistics in analyzing Big Data with a focus on the university context. Using statistical methods and Big Data analysis techniques, this research details the implementation of statistics to untangle and unravel the mysteries of complex data. Key findings include the identification of factors that influence students' academic performance and the unique contribution of statistics to the understanding of dynamics in the context of higher education. Through comparisons with previous research, the study also highlights the relevance of the findings to previous literature. A discussion of the challenges and obstacles in Big Data analysis provides insight into the complexity of the process. Research implications include the contribution of statistics to policy formulation and university practice. Conclusions and suggestions for future research complete a comprehensive picture of the role of statistics in unraveling the mysteries of data in the era of Big Data.